1986
DOI: 10.1128/aem.52.3.413-419.1986
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Purification of Glutamine Synthetase from Clostridium acetobutylicum

Abstract: A glutamine synthetase (GS) gene, glnA, from the gram-positive obligate anaerobe Clostridium acetobutylicum was cloned on recombinant plasmid pHZ200 and enabled Escherichia coli glnA deletion mutants to utilize (NH4)2SO4 as a sole source of nitrogen. The cloned C. acetobutylicum gene was expressed from a regulatory region contained within the cloned DNA fragment. ginA expression was subject to nitrogen regulation in E. coli. This cloned glnA DNA did not enable an E. coli ginA ntrB ntrC deletion mutant to utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The C. acetobutylicum insert DNA was recloned in pLAFRI in the opposite orientation, and the resulting recombinant plasmid also complemented the leuB6 mutation in E. coli HB101, indicating transcription from the C. acetobutylicum promoter. This was also found by Usdin et al [8] in the case of the glutamine synthetase gene of C. acetobutylicum.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The C. acetobutylicum insert DNA was recloned in pLAFRI in the opposite orientation, and the resulting recombinant plasmid also complemented the leuB6 mutation in E. coli HB101, indicating transcription from the C. acetobutylicum promoter. This was also found by Usdin et al [8] in the case of the glutamine synthetase gene of C. acetobutylicum.…”
Section: Discussionsupporting
confidence: 80%
“…In previous studies it was shown that some Clostridium genes can be identified through expression in Escheriehia coli. These include genes coding for amino acid synthesis [4][5][6][7][8], catabolic activities [9][10][11], electron transport [12], and extracellular enzymes [4, 6,7,[13][14][15]. In this study we have used the same strategy to screen a gene library of C. acetobutylicurn ATCC824 in E. coli MC1061 for starch hydrolyzing clones.…”
mentioning
confidence: 99%
“…Until recently it seemed that bacteria had two types of GS, termed GSI and GSII, but recently a third bacterial GS, GSIII has been described. GSI is the typical bacterial GS which is present in the Enterobacteriaceae [8,9], Vibrio [10], Thiobacillus [11], Bacillus [12][13][14][15][16], Clostridium [17,18], and Streptomyces [19,20]. GSII is similar to the eukaryotic GS [21] and is found in members of the Rhizobiaceae, Frankiaceae and Streptomyces [22][23][24][25][26] which are characterized by having both GSI and GSII.…”
Section: Structure Of Gs Enzymesmentioning
confidence: 99%
“…GSI enzymes can be divided into two groups depending on whether they are modified by the adenylylation system. The GSI enzymes from the Gram-negative Enterobacteriaceae, Vibrio [11] and ThiobaciUus [10], are regulated by this system, whereas the GSI enzymes from the Grampositive bacteria, Bacillus [13,33,34] and Clostridium [17,35], are not regulated by adenylylation. However, regulation by adenylylation is not necessarily correlated with the Gram-stain reaction since GS1 from the Gram-positive Streptomyces coelicolor is regulated by adenylylation [36].…”
Section: Structure Of Gsi Enzymesmentioning
confidence: 99%
“…) or by the assimilation of inorganic nitrogen compounds such as ammonia (NH 4 + ) (Usdin et al . ). The transport and biosynthesis of amino acids is also of paramount importance.…”
Section: Introductionmentioning
confidence: 97%